Progressive damage analysis of three-dimensional braided composites under flexural load by micro-CT and acoustic emission. (15th October 2019) - Zhang, Peng-fei; Zhou, Wei; Yin, Han-fei; Shang, Ya-jing
Abstract: The effect of the load-bearing direction on the progressive bending damage of three-dimensional (3D) five-directional braided composites remains to be further discussed. To address this issue, two kind of samples, longitudinal and transverse, are experimentally tested three-point bending method. Simultaneously, the damage evolution behaviors are monitored by acoustic emission (AE) technology. Furthermore, X-ray micro-computed tomography (micro-CT) techniques are employed to identify the internal damage initiation/evolution and distribution characteristics of 3D braided composites. The microscopic damage morphology observed by micro-CT can be well correlated with the variation characteristics of the collected AE parameters. Through analyzing the experimental results, the damage of the longitudinally load-bearing specimen is mainly caused by the damage of the fiber and yarn, while the damage forms of transverse load-bearing materials are mainly fiber slip, interface debonding, matrix cracking and fiber fracture. Since the axial yarns and braided fibers of the longitudinal load-bearing specimens have played a supporting role, the bearing performance and the deformation resistance are superior to the transverse load-bearing material. The proposed combination of AE and micro-CT can provide a reference for monitoring the damage process and predicting the failure.